Gallic Acid Ameliorates Atopic Dermatitis-Like Skin Inflammation Through Immune Regulation in a Mouse Model - Hu G (Dove Medical Press, 2021)
Guohong Hu, Xiansheng Zhou Dermatology Hospital of Jiangxi Province, Nanchang, 330001, Jiangxi, People’s Republic of ChinaCorrespondence: Guohong HuDermatology Hospital of Jiangxi Province, No. 388 Yingbin North Road, Nanchang, 330001, Jiangxi, People’s Republic of ChinaTel +86-791-85221034Email 2009020212@st.btbu.edu.cnBackground: Gallic acid (GA) has an anti-inflammatory effect by regulating inflammatory molecules. This study aimed to investigate the effect of GA on atopic dermatitis (AD)-like skin inflammation.Methods: 4-dinitrochlorobenzene (DNCB) was used to induce an AD-like skin inflammation model. The effect of GA on DNCB-induced inflammation was assessed by measuring the thickness and histopathological examination of the ear. Serum IgE and TNF-α levels were detected. The effect of GA on lymph nodes was determined by measuring the weights and mRNA/protein expression levels of TNF-α, IL-4, IFN-γ and IL-17. Ratio of Treg cells and Th17 cells was also analyzed.Results: It was found that the thickness and pathology of the ear were significantly improved by GA in the DNCB-induced mice. Serum IgE and TNF-α levels were significantly reduced in GA-treated model mice compared to the model group. GA treatment lowered the weight of lymph node and the expression of mRNAs of TNF-α, IL-4, IFN-γ, and IL-17 of lymph node. In the ear, inflammatory factors (IL-4, IL-5, IL-17, or IL-23) showed a significant decrease in GA-treated model mice versus model mice, while the expression levels of IL-10 and TGF-β showed a great increase in GA-treated model mice. ROR-γt showed a decrease in GA-treated model group, along with an increase expression of SOCS3.Conclusion: GA could ameliorate AD-like skin inflammation possibly through Th17 mediated immune regulation in a DNCB-induced mouse model.Keywords: 4-dinitrochlorobenzene, DNCB, Th17, IL-10, TGF-β, IFN-&#x03B3